Redescription and typification of Dendropanax umbellatus (Araliaceae) - Fernandez-Hilario, Robin; Villanueva-Espinoza, Rosa; Fack, Vinciane (Phytotaxa, 2020)
The relationship between Dendropanax umbellatus and Gilibertia pavonii has remained uncertain for more than one hundred years, causing the second species to be considered a synonym of the first one. In order to provide nomenclature and taxonomic clarity, we herein discuss the history of both species and do the necessary typifications.